Chronic periodontitis and its correlation with socio-demographic and oral health parameters: A retrospective study in adult population - Yaacob, Munirah; Fazid, Nurul Farahin; Sao'di, Siti Mahirah; Husain, Juzaily; Muhammad Ali, Suhaila (JK Welfare & Pharmascope Foundation, 2019)
Chronic periodontitis is the second most common oral disease worldwide. It is a multifactorial disease with bacterial plaque as the necessary factors, however other factors such as age, systemic conditions and social habits do play a determining role in the development of periodontitis. Therefore, this study evaluated the correlation between severity of chronic periodontitis with a series of socio-demographic background and clinical variables. This was a retrospective, observational study of chronic periodontitis population that attended IIUM Dental Clinic from the year 2014 to 2017. The data was extracted from patients’ case records systematically using structured data extraction form. Only case records with full clinical history and periodontal charting were undertaken as samples. IBM SPSS-24 was used for data analysis. Chi-square (χ2 ) and Mann-Whitney U tests were applied to infer the above relationship. The result of analysis revealed that over four years, 157 adults were diagnosed with chronic periodontitis, which comprised of 68.8% who suffered with severe form. The mean age group was 48.6±11.55 years old with the majority of them were Malays, male, and aged between 50 to 64 years old. Those who are professional workers, suffered with systemic diseases and were addicted to tobacco exhibited more severe disease though statistically not significant. Patients with moderate and severe chronic periodontitis showed greater plaque deposits and have deeper periodontal pockets than those with mild form (p<0.05). They also presented with more tooth lost. Severe chronic periodontitis was found prevalent in the studied population. As conclusion, the clinical and socio-demographic characteristics showed non-significant correlations with the severity of the disease except for gender, plaque control levels, and number of deep pocket sites. Future studies should consider including more sample size from multicenter population.